2020
DOI: 10.17576/malim-2020-2101-08
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence and the Press Effects on Prehospital Cardiopulmonary Resuscitation: Attitudes of a Group of Emergency Caregivers

Abstract: There have been many studies regarding family presence during cardiopulmonary resuscitation and most of them are about emergency services or intensive care units. However, the issue has not been studied enough in terms of prehospital emergency medicine and the perspective of prehospital emergency caregivers. In this study, it is aimed to present the attitudes of a group of prehospital emergency care professionals to family presence and the press effects during prehospital cardiopulmonary resuscitation. The dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Although it is a common situation in prehospital emergency medicine practice, there are not enough studies on it. 10 In this study, 84.5% of the participants stated that they performed witness resuscitation in the pre-hospital setting. This supports the view that witnessed resuscitation in the prehospital setting is a common practice among prehospital emergency medicine professionals and is an ethical issue that should be studied.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although it is a common situation in prehospital emergency medicine practice, there are not enough studies on it. 10 In this study, 84.5% of the participants stated that they performed witness resuscitation in the pre-hospital setting. This supports the view that witnessed resuscitation in the prehospital setting is a common practice among prehospital emergency medicine professionals and is an ethical issue that should be studied.…”
Section: Discussionmentioning
confidence: 72%
“…16 In other study conducted by Erbay H. , it was found that witnessed resuscitation performed in the prehospital area negatively affects the performance of the healthcare team and causes anxiety. 10 In contrary, Abuzeyad FH. et al found that witnessed resuscitation did not have a negative impact on health care workers.…”
Section: Professional Autonomy In Witnessed Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation